2009
DOI: 10.1245/s10434-009-0662-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in 77 Curative Chest Wall Resections for Isolated Breast Cancer Recurrence

Abstract: BackgroundFull-thickness chest wall resection (CWR) is the preferred treatment for breast cancer (BC) patients with extensive isolated locoregional recurrence. It remains a challenge to select patients that will benefit most from this treatment. The aim of this study was to define prognostic factors in patients who undergo CWR with curative intent.MethodsBC patients who underwent a CWR with curative intent for recurrence of disease between 1986 and 2006 were included in this retrospective study. Twenty-two fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Survival after second-IBTR ranges from a median of 33 months 19 to 80.7% at 5 years 20 . Treatment of post-mastectomy nodal or chest wall recurrences is associated with lasting local control of disease in about 50% of cases, but no series provide outcomes following a second-ILRR 6,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Survival after second-IBTR ranges from a median of 33 months 19 to 80.7% at 5 years 20 . Treatment of post-mastectomy nodal or chest wall recurrences is associated with lasting local control of disease in about 50% of cases, but no series provide outcomes following a second-ILRR 6,21 .…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, a definite surgical resection is the essential factor for long-term survival. Several studies showed that in addition to a disease-free interval >2 years and extent of the regional recurrence (14,34), the radicality of an extensive resection had a benefit on prognosis, both after mastectomy (35,36) and after BCT in primary disease (12,13). Consequently, we may suggest that every fourth patient (25.6%) in the present study population profited from the MRI findings: by detection of either contralateral disease or additional lymph nodes and thoracic wall lesions resulting in improved treatment planning, more extensive surgery, and additional radiotherapy of occult lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[12-14] Loco-regional recurrence of breast cancer in the chest wall occurs in approximately 9% of patients undergoing breast conservation therapy. [14] Multi-modality treatment including chemotherapy, radiation, and surgery is typically employed.…”
Section: Surgical Resection Of the Irradiated Chest Wallmentioning
confidence: 99%
“…[12-14] Loco-regional recurrence of breast cancer in the chest wall occurs in approximately 9% of patients undergoing breast conservation therapy. [14] Multi-modality treatment including chemotherapy, radiation, and surgery is typically employed. Although there is some controversy regarding the benefit of surgery compared with systemic therapy and radiation therapy in estrogen receptor-negative breast cancer, surgical resection is often carried out after radiation therapy has already been administered to the chest wall.…”
Section: Surgical Resection Of the Irradiated Chest Wallmentioning
confidence: 99%